Education Budget Politics and Access Inequality in Underdeveloped Regions - Rizkiyah Purnama; Zainal Efendi Hasibuan (Rahis Cendekia Indonesia, 2025)
It is not only related to academic achievement but also reflects the institution's ability to interact with and contribute to the community. This article aims to examine strategies for improving the quality of educational institutions and how they can expand their participation in social development. Through a qualitative-descriptive approach, it was found that the synergy between internal management, professional educators, relevant curricula, and community involvement is the key to the success of educational institutions that are both high-quality and socially impactful. Educational institutions must be able to serve as centers of learning as well as agents of social change in their environments.